Implementasi SMARCOS: Smart Water Conditioning System Berbasis Web-IoT di Balai Benih Ikan Kecamatan Mijen Semarang - Anan Nugroho; Mona Subagja; Syahroni Hidayat; Agung Budiwirawan; Ledi Diyanasari; Jhonatur Stheven Simanjuntak; Tri Agus Wahyudi; Akmal Fikri (Indonesian Journal Publisher, 2025)
Effective water quality management is crucial for fish hatcheries to ensure survival and productivity. At the Fish Hatchery Center (BBI) Cangkiran Mijen, water quality monitoring is still conducted manually, leading to unstable pond conditions. To improve monitoring efficiency, SMARCOS (Smart Water Conditioning System) was developed as a Web-IoT-based system for automated monitoring of water parameters such as pH, oxygen, and temperature. The program involved pond data collection, expert consultation, system design, testing, implementation, and partner training. Evaluation was conducted through satisfaction surveys and system performance monitoring. Results showed that SMARCOS effectively corrected water quality parameters automatically, enhanced monitoring efficiency, and provided easy access to information via an IoT-based website. Surveys indicated that partners were satisfied with the system’s usability. The adoption of IoT for water quality monitoring significantly improved the efficiency and accuracy of hatchery pond management. Training sessions also increased partner understanding of IoT technology. The success of SMARCOS demonstrates that IoT can be an innovative solution for fisheries modernization, with potential replication in other hatcheries to enhance productivity and efficiency in aquaculture.